Kajian Gangguan Fungsi Paru Pada Pekerja Pengelasan Di Kecamatan Mertoyudan Kabupaten Magelang - Sukawati, Endang; Setiani, Onny; Nurjazuli, Nurjazuli (Jurnal Kesehatan Lingkungan Indonesia, 2014)
Background: Welders are at high risk for suffering from pulmonary function disorders. A preliminary study revealed that as many as 50% of welders suffered from this kind of disease. This study aimed to explain risk factors associated with the occurrence of pulmonary function disorders among welders in their workshops. Methods: It was observational research with cross-sectional approach. Number of samples ware 47 welders worker at industries. Pulmonary function testing was measured using Spirometer Lab III. While, dust levels inside workplace were measured using Low Volume Sampler (LVS). Results: Factors of dust levels (p=0.475; PR=1.278), duration of exposure (p=0.697; PR=1.231), nutritional status (p=0.077; PR=1.913) and number of cigarettes more than 9 rods a day (p=0.037; PR=1.765) had no significant association with pulmonary function disorders. On the other hand, factors of age (p=0.011; PR=1.965), length of work more than 5 years (p<0.001; PR=9.257), length of smoking (p=0.024; PR=1.878) had significant association with pulmonary function disorders. Furthermore, multivariate analysis showed that the length of work more than 5 years was the most dominant variables influencing pulmonary function disorders (p=0.007 and Exp(B) with 95%CI=24,158 (2.348 – 248.516). Conclusion: Welders who have been working more than 5 years are 24 times as likely to have pulmonary function disorders as those who have been working less than or equal to 5 years.    Keywords: Dust Levels, Pulmonary Function Disorders